Effectiveness of Supportive Therapy and Economic Token Therapy in Reducing The Symptoms of Self-Care Deficit, Based on The Peplau Nursing Model - Nofrida Saswati Nofi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Self-care deficit is a nursing diagnosis in which the client experiences an inability to independently perform personal hygiene, dress, eat and defecate. Therefore, interventions are needed to address clients with self-care deficits. One of the interventions carried out is supportive therapy and token economy using the Peplau interpersonal nursing model approach. The purpose of this study was to analyse the effectiveness of supportive therapy and token economy in reducing signs and symptoms of self-care deficits based on the Peplau interpersonal nursing model. Methods: The research design was a quasi-experimental study using a two group pre-post design. The sample in this study amounted to 40 respondents, 20 intervention groups, and 20 control groups according to the research criteria. This research was conducted in July-August 2021. The sampling technique was carried out by purposive sampling. The data was analysed by univariate and bivariate with a t-dependent test. Results: The results of the study showed that there was an increase in self-care before and after being given supportive therapy and economic tokens in the intervention group with a value before 133.60 to 140.05. A statistical test obtained p-value = 0.000 which means that there is an effect of supportive therapy and economic tokens in reducing signs of symptoms Of  self-care deficit. The results obtained in the control group after being given supportive therapy with values before 128.85 to 138.55 and statistical tests obtained p-value = 0.041, meaning that there is an effect of supportive therapy in reducing symptoms of self-care deficits. Conclusion: There is an effect of supportive therapy and token economy on improving self-care in self-care deficit clients. Supportive therapy and token economy are recommended for self-care deficit clients to improve self-care abilities.@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-536858881 -1073732485 9 0 511 0;}@font-face {font-family:"Gill Sans MT"; panose-1:2 11 5 2 2 1 4 2 2 3; mso-font-charset:77; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:3 0 0 0 3 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-priority:1; mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:none; text-autospace:none; font-size:11.0pt; font-family:"Arial",sans-serif; mso-fareast-font-family:Arial; mso-ansi-language:EN-US; mso-fareast-language:EN-US; mso-bidi-language:EN-US;}p.Default, li.Default, div.Default {mso-style-name:Default; mso-style-unhide:no; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; mso-layout-grid-align:none; text-autospace:none; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:Calibri; color:black; mso-ansi-language:EN-US; mso-fareast-language:EN-US;}span.jlqj4b {mso-style-name:jlqj4b; mso-style-unhide:no;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:11.0pt; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:EN-US; mso-fareast-language:EN-US;}.MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;}div.WordSection1 {page:WordSection1;}